Kualitas Fisik, Kimia, Mikrobiologi Susu Sapi pada Peternakan Sapi Perah di Kecamatan Caringin Kabupaten Bogor: Physical, Chemical, and Microbiology Qualities of Cow’s Milk in Dairy Farm in Caringin District Bogor (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Each type of milk has different qualities depending on its physical, chemical, and microbiological properties. The aim of this study was to determine the physical, chemistry, and microbiological quality of cow’s milk in dairy farm in Caringin District, Bogor. The milk samples came from three dairy farms in Caringin District, Bogor. Physical properties that observed were pH and density. Chemical properties that observed were BKTL, levels of protein, fat, lactose tested using Lactoscan Milk Analyzer. Microbiological properties that observed were total plate count (TPC) and number of Staphylococcus aureus (S. aureus) which test method refers to SNI 2897:2008. The results showed that quality of the physical and chemical properties of cow's milk in three dairy farms in Caringin District, Bogor according to SNI 3141.1: 2011. Microbiological quality (TPC) of farms A and B were according to SNI 3141.1:2011. TPC of dairy farm A is 1.9 x 105CFU/ml and dairy farm B 2.6 x 105 CFU/ml, whereas dairy farm C wasn’t according to SNI 3141.1:2011 with average of TPC 2.2 x 106CFU/ml. Number of S. aureus in milk in dairy farms A, B and C wasn’t according to SNI 3141.1:2011. Average number of S. aureus on dairy farm A was 1.3 x 103 CFU /ml, dairy farm B 1.4 x 103 CFU/ml and dairy farm C 2.4 x 103 CFU/ml. Cow's milk from three dairy farms in Caringin District, Bogor were still suitable for consumption by heating it before consumption to kill microbial contamination in it.